Validated TRNSYS model for forced circulation solar water heating systems with flat plate and heat pipe evacuated tube collectors - MC CORMACK, SARAH (Elsevier, 2011)
This paper presents a validated TRNSYS model for forced circulation solar water heating systems used in temperate climates. The systems consist of two flat plate collectors (FPC) and a heat pipe evacuated tube collector (ETC) as well as identical auxiliary components. The systems were fitted with an automated unit that controlled the immersion heaters and hot water demand profile to mimic hot water usage in a typical European domestic dwelling. The main component of the TRNSYS model was the Type 73 FPC or Type 538 ETC. A comparison of modelled and measured data resulted in percentage mean absolute errors for collector outlet temperature, heat collected by the collectors and heat delivered to the load of 16.9%, 14.1% and 6.9% for the FPC system and 18.4%, 16.8% and 7.6% for the ETC system respectively. The model underestimated the collector outlet fluid temperature by -9.6% and overestimated the heat collected and heat delivered to load by 7.6% and 6.9% for the FPC system. The model overestimated all three parameters by 13.7%, 12.4% and 7.6% for the ETC system.
PUBLISHED
Keywords: Energy and fuels; Solar water heater